A nomogram to predict node positivity in patients with thin melanomas helps inform shared patient decision making. Issue 7 (10th October 2019) - Friedman, Chloe; Lyon, Madison; Torphy, Robert J.; Thieu, Daniel; Hosokawa, Patrick; Gonzalez, Rene; Lewis, Karl D.; Medina, Theresa M.; Rioth, Matthew J.; Robinson, William A.; Kounalakis, Nicole; McCarter, Martin D.; et al.
Abstract: Objective: To develop a nomogram to estimate the probability of positive sentinel lymph node (+SLN) for patients with thin melanoma and to characterize its potential impact on sentinel lymph node biopsy (SLNB) rates. Methods: Patients diagnosed with thin (0.5–1.0 mm) melanoma were identified from the National Cancer Database 2012 to 2015. A multivariable logistic regression model was used to examine factors associated with +SLN, and a nomogram to predict +SLN was constructed. Nomogram performance was evaluated and diagnostic test statistics were calculated. Results: Of the 21 971 patients included 10 108 (46.0%) underwent SLNB, with a 4.0% +SLN rate. On multivariable analysis, age, Breslow thickness, lymphovascular invasion, ulceration, and Clark level were significantly associated with SLN status. The area under the receiver operating curve was 0.67 (95% confidence interval, 0.65‐0.70). While 15 249 (69.4%) patients had either T1b tumors or T1a tumors with at least one adverse feature, only 2846 (13.0%) had a nomogram predicted probability of a +SLN ≥5%. Using this cut‐off, the indication for a SLNB in these patients would be reduced by 81.3% as compared to the American Joint Committee on Cancer 8th edition staging criteria. Conclusions: The risk predictions obtained from the nomogram allow for more accurate selection of patients who could benefit from SLNB.